Legislative information on Brazilian women’s rights in the making: How to organize according to the 2030 Agenda - Martellote Viola, Carla Maria (Advanced Notes in Information Science, 2024)
The article presents a theoretical, methodological, and practical framework for the study of legislative information pertaining to the representation and organization of Brazilian women’s rights in a state of flux. The objective is to present a categorization system that can be used to classify legislative proposals currently being considered by the Chamber of Deputies, which pertain to women’s rights under construction. This will demonstrate legislative progress or setbacks in relation to the 2030 Agenda, in particular Sustainable Development Goal 5 (SDG 5) and its targets. The methodology establishes arguments and structures actions that facilitate the design of applied research projects within the field of information science. A bibliographic approach is employed to construct the fundamental theory, while exploratory research and a qualitative methodology are utilized to generate categories and explanatory notes. These are based on the tenets of the knowledge organization and in alignment with the assertions set forth in the 2030 Agenda. The guiding thematic units are based on a quantitative analysis of the subjects found in the legislative data and metadata of 1,041 legislative proposals initiated and underway in the 56th Legislature (2019–2023). Consequently, 12 categories were devised. It can be concluded that the creation of a categorization for Brazilian legislative proposals on the rights of Brazilian women under construction, with a view to the 2030 Agenda, addresses the necessity for legislative information on women’s development. Furthermore, it reveals the necessity for public policies and transparency of information in order to gauge the intentions and attention of the Brazilian Parliament and to meet the goals of the SDGs.